Advancing Alzheimer’s Diagnosis: The Role of AI - A Review - Rehan, Dominka; Solisch, Sven; Blazhkova , Anna; Susłow, Anna; Szwed, Adam; Szczęsna, Ewa (Journal of Education, Health and Sport, 2025)
Introduction: Alzheimer’s disease (AD) is a progressive neurodegenerative disease that accounts for more than half of all cases of dementia worldwide. An aging society therefore poses a huge challenge to medicine. The exact mechanism responsible for this disease is still not fully understood. However, theories of neurodegeneration related to the deposition of pathological proteins in the brain and the imbalance between individual neurotransmitters have allowed the development of effective diagnostic methods - laboratory determination of specific biomarkers (tau protein, β-amyloid) and their marking using PET (Amyloid PET, Tau PET). Magnetic resonance imaging (MRI) is also important in diagnostics. Artificial intelligence (AI) is a promising, new, and rapidly developing path that can significantly affect the diagnostic process of Alzheimer’s disease. Purpose of the study: This review examines the role of AI in diagnosing Alzheimer’s disease. Materials and methods: A comprehensive literature review was conducted, analyzing 63 studies from the PubMed database (in English, up to December 2024) that assessed the effectiveness, methods, and prospects of AI in the diagnosis of Alzheimer’s disease. Conclusions: Share of AI in the diagnosis of Alzheimer’s disease is extremely promising. AI used in neuroimaging, genetics, and behavioral biomarkers shows great potential diagnostic. AI-based tools are extremely promising because they can be non-invasive and highly sensitive biomarkers. Optical coherence tomography (OCT) and OCT angiography (OCTA) combined with AI models offer an opportunity for cost-effective and rapid diagnostic pathways for AD. This review presents evidence that artificial intelligence is a key factor in transforming AD diagnostics into modern diagnostics that enable earlier detection and treatment of the disease which may consequently positively impact the quality of life of AD patients and their caregivers.